The role of neutrophil activation in determining the outcome of pregnancy and modulation by hormones and/or cytokines. (13th March 2019) - Hahn, S; Hasler, P; Vokalova, L; van Breda, S V; Lapaire, O; Than, N G; Hoesli, I; Rossi, S W
Summary: Neutrophils are often exclusively considered as a first-line innate immune defence, able to rapidly kill or trap pathogens and causing in case of over-activation tissue damage. In the female reproductive tract, however, the presence and activity of neutrophils seems to be tightly regulated. Major players in orchestrating this regulation are cyclical steroid sex hormones present during the menstrual cycle and pregnancy. This review describes the role of sex hormones in regulating directly or indirectly the functionality of neutrophils, the role of neutrophils during fertilization and pregnancy and in controlling viral, fungal and bacterial infection. This review also discusses the consequence of overt neutrophil activation in pregnancy pathologies. Graphical Abstract: